MANAJEMEN PENDIDIKAN ISLAM TENTANG KEPEMIMPINAN KIAI DI PONDOK PESANTREN TAHFIDZ DAARUL QUR’AN CIPONDOH TANGERANG - Luqmanul Hakim Muttaqin; Muhammad Haekal; Ibrahim Ibrahim; Ratna Tri Utami (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
The objective of this research was to disclosure comprehensive the leadership of Kiai (Islamic leader) in leading the implementation of Islamic boarding school. It was qualitative research by using case study in tahfidz Daarul Qur’an boarding school, Tangerang, Banten Indonesia in 2013.The data were collected through partisipant observation using interview, observation, document study and recordings. The data analysis and interpretation indicates that (1) the styles of Kiai’s leadership to fulfill the types of leadership, they are charismatic, democratic and situational, (2) the influences of Kiai’s leadership shown by a formal strength as the founder of boarding school, have a high, popular and charismatic scientific religion, (3) the functions of Kiai’s leadership includes the function of briefing, exemplary, decision maker, problem solving and guiding, (4) the impacts of Kiai’s leadership gives the positive impacts with the numbers of Hafidz Quran (Koran Memorizer) and the adequate facilities and infrastructures. The negative impacts are with the mode of fraud business.The result of the research gives the recommendation for the Kiai’s leadership in leading the boarding school can be accompanied by the strength team in applying the program of tahfidz in the boarding school and it needs to continue the next research connected to Kiai’s leadership and more portions of activities.